SELF-ESTEEM AS A PREDICTOR OF PUBLIC SPEAKING ANXIETY AMONG POSTGRADUATE STUDENTS IN AL-HIKMAH UNIVERSITY ILORIN, NIGERIA - Kamaldeen, Rahmat Tinuke; Osere, M. O. (Universitas Pendidikan Indonesia, 2025)
Public speaking skills are essential for postgraduate students, thus, many individuals still face challenges with anxiety when it comes to presenting their ideas or research findings in public settings. Therefore, this study investigates the relationship between self-esteem and public speaking anxiety among postgraduate students at Al-Hikmah University, Ilorin. A descriptive survey design was employed, with data collected from 96 postgraduate students which were properly filled out of the 100 administered. The results revealed that 56.3% of the students experience low levels of public speaking anxiety, 29.2% moderate levels, and 14.6% high levels. Pearson Product-Moment Correlation (PPMC) was used to analyze the relationship between self-esteem and public speaking anxiety. The findings indicated a weak negative correlation (r = -0.109) between the two variables, with a p-value of 0.290, which is greater than the significance level of 0.05. Consequently, the null hypothesis was not rejected, confirming that there is no significant relationship between self-esteem and public speaking anxiety among postgraduate students. Based on these findings, it is recommended that the university implement public speaking training workshops and provide counseling services to support students with high levels of public speaking anxiety.